The The Construction of Husein Ja’far’s Character in the Digital Da’wah Space: A Critical Discourse Analysis of “Pemuda Tersesat” Content: Konstruksi Penokohan Husein Ja’far dalam Ruang Dakwah Digital: Analisis Wacana Kritis pada Konten Pemuda Tersesat - Ruhul Qudus, Muhammad; Kholifah, Siti; Purnomo, Mangku (Communicatus: Jurnal Ilmu komunikasi, 2025)
This study explores how Husein Ja’far constructs his persona as a moderate, relatable, and intellectual preacher through the YouTube program Pemuda Tersesat. Using Norman Fairclough’s Critical Discourse Analysis, the research examines textual, discursive, and social dimensions to uncover how language, humor, and ideology contribute to shaping his public image. The findings reveal that Husein Ja’far integrates humor techniques such as satire and callback, along with informal and accessible language, to engage effectively with young audiences. His approach reflects the principles of tawazun (balance) and i‘tidal (straightforward and decisive), emphasizing a moderate Islamic perspective that bridges spirituality with rational and psychological understanding. Beyond digital communication, his influence is evident in the social movement Celengan Pemuda Tersesat, which mobilized collective empathy and solidarity during the COVID-19 pandemic. This study concludes that Pemuda Tersesat exemplifies a transformative form of digital da’wah, where religious discourse, media engagement, and social awareness intersect to redefine religious authority in Indonesia’s digital age.